Diagnostic value of stool antigen and antibody tests for Helicobacter pylori infection in Turkish children with upper gastrointestinal complaints before and after eradication - Tiryaki, Zehra; Yilmaz-Ciftdoğan, Dilek; Kasirga, Erhun (The Turkish Journal of Pediatrics, 2010)
The aim of this study was to evaluate the diagnostic value of Helicobacter pylori stool antigen (HpSA) and serologic tests before and after eradication therapy for H. pylori in Turkish children in our region with upper gastrointestinal complaints. In this study, 87 children with upper gastrointestinal complaints and 95 children with various symptoms without gastrointestinal complaints were enrolled. H. pylori infection was detected by urea breath test (UBT). HpSA and H. pylori immunoglobulin G (HpIgG) tests were applied to all the children. Eradication treatment was given to the 34 H. pylori-positive children. The UBT was positive in 43 of 87 children (49.4%) with upper gastrointestinal complaints. The sensitivity and specificity of the HpSA in children with upper gastrointestinal complaints were 86% and 84.1%, respectively, and those for the HplgG were 76.7% and 90.9%, respectively. After eradication, the overall HpSA test sensitivity and specificity values were detected as 88.9% and 84%, respectively, and those for the HpIgG were 77.8% and 36%, respectively. The HpSA test is highly sensitive and specific for the diagnosis of H. pylori and for confirming eradication in Turkish children with upper gastrointestinal complaints. However, serology is not a reliable method for the diagnosis of H. pylori infection or for confirming eradication in children.